Assessing prevention measures and sin nombre hantavirus seroprevalence among workers at Yosemite National Park. Issue 6 (5th May 2015) - Wilken, Jason A.; Jackson, Rebecca; Materna, Barbara L.; Windham, Gayle C.; Enge, Barryett; Messenger, Sharon; Xia, Dongxiang; Knust, Barbara; Buttke, Danielle; Roisman, Rachel; for the Yosemite Hantavirus Outbreak Investigation Team
<x xml:space="preserve">Abstract</x> Background During 2012, a total of 10 overnight visitors to Yosemite National Park (Yosemite) became infected with a hantavirus (Sin Nombre virus [SNV]); three died. SNV infections have been identified among persons with occupational exposure to deer mice (Peromyscus maniculatus). Methods We assessed SNV infection prevalence, work and living environments, mice exposures, and SNV prevention training, knowledge, and practices among workers of two major employers at Yosemite during September–October, 2012 by voluntary blood testing and a questionnaire. Results One of 526 participants had evidence of previous SNV infection. Participants reported frequently observing rodent infestations at work and home and not always following prescribed safety practices for tasks, including infestation cleanup. Conclusion Although participants had multiple exposures to deer mice, we did not find evidence of widespread SNV infections. Nevertheless, employees working around deer mice should receive appropriate training and consistently follow prevention policies for high‐risk activities. Am. J. Ind. Med. 58:658–667, 2015. © 2015 Wiley Periodicals, Inc.